Butyrylcholinesterase level in poisoned patients by phosphide compounds - Saeed Afzali; Seyed Kazem Taheri; Mohamadali Seifrabiei (Babol University of Medical Sciences, 2019)
Background: Metal phosphides are widely used as a rodenticide and insecticide and poisoning with these substances has a very high mortality. The aim of this study was to evaluate the butyrylcholinesterase (BuCh) level in poisoning with metal phosphides. Methods: In this case series study, 60 poisoned patients with zinc phosphide (ZnP) and aluminum phosphide (ALP) who was admitted to poisoning ward in Hamadan, Iran, enrolled in the study and BuCh level was measured. The sex, age, amount of ingestion, time of consumption, signs and symptoms, ECG and arterial blood gas (ABG) changes and clinical outcomes were evaluated. Results: Most (58.3%) patients were males, the mean age was 32.76±17.65 years. The average amount of ingestion was 7.5±4.6 and 2.5±2.96 gr for ZnP and ALP, respectively. Most signs and symptoms were hypotension (97%), nausea and vomiting (82%) and abdominal pain (32%). The average amount of BuCh level in all patients was 5163.25±2158.31 U/L, that's while in ZnP and ALP poisoned patients was 5608±1577 U/L and 4721.46±2562U/L respectively. The most dysrhythmia (26.7%) was sinus tachycardia. Acidosis was seen in 33.3% of patients. 14 patients died after hospital admission, which caused a 23.3% fatality rate. Conclusion: Our results showed that, there was no significant change in BuCh level in poisoned patients with phosphide compounds.